GREEN CAMPUS AND ITS IMPACT ON THE QUALITY OF LIFE OF STUDENTS AT THE UNIVERSITY OF BAGHDAD - JASIM, SADA; ANNON, NADIA (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate relationship between the utilization of the College of Agricultural Engineering Sciences students for green spaces and their impact on their life quality in its cognitive and social dimensions. The research adopted the descriptive analytical approach to the reality of the green spaces most frequented by students through a field survey, in addition to adopting a questionnaire form distributed among a sample of college students from various departments. after collecting and transcribing the data, it was analyzed statistically and the significant differences between the means were compared with the Least Significant Difference (L.S.D.) test. Results showed that the most important thing provided by the green space environment at the university for students to improve their quality of life was their feeling of joy and vitality as a result of the influence of the colors of the plant canopy of various types and their flower colors, as well as the various forms water elements of the water canal surrounding the academic campus of the university campus and the fountains and lakes from which their water is derived, which enhanced the students' feel of beauty, relax, and reduced stress in them which consequently encouraged them to walk around and spend an enjoyable and valuable time in various academic and social activities, thus improving their academic performance and their sense of responsibility towards preserving this environment.